A Copyright Tale of Two Collecting Societies: Public Performance Malaysia Sdn Bhd & Anor v PRISM Berhad - San, Tay Pek (Journal of Malaysian and Comparative Law, 2016)
Under the Copyright Act 1987 (‘CA 1987’), a society or organisation which is set up to negotiate and grant copyright licences for and on behalf of copyright owners is referred to as a ‘licensing body’. Essentially, a licensing body grants licences and collects royalty on behalf of its members who are copyright owners. In Public Performance Malaysia Sdn Bhd & Anor v PRISM Berhad,1 the High Court presided over a dispute between two licensing bodies which centred on the issue of copyright ownership in a number of licensing documentations used in the course of royalty collection. It is the first reported case involving licensing bodies in Malaysia